1997
DOI: 10.1021/la9606207
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nanoparticles in Microemulsions:  A Monte Carlo Study of the Influence of the Synthesis Variables

Abstract: Monte Carlo simulations were performed to study the formation of nanoparticles in microemulsions. The influence of the following parameters on particle size distribution (PSD) was investigated:  number of reagent molecules per droplet, surfactant film flexibility, droplet size, presence or absence of autocatalysis by the product, and the fraction of bulk volume made up by droplets. It was found that autocatalyzed reactions with high reagent concentrations and low surfactant film flexibility afforded bimodal PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
94
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 31 publications
3
94
0
Order By: Relevance
“…Below this size, the nuclei dissolve, because of their large Laplace pressure. Above this size, the nuclei grow continuously to reduce their surface energy by different mechanisms, such as autocatalysis or Ostwald ripening, [7] until their growth is stopped by templates or capping agents, for example.…”
mentioning
confidence: 99%
“…Below this size, the nuclei dissolve, because of their large Laplace pressure. Above this size, the nuclei grow continuously to reduce their surface energy by different mechanisms, such as autocatalysis or Ostwald ripening, [7] until their growth is stopped by templates or capping agents, for example.…”
mentioning
confidence: 99%
“…A consequence of this phenomenon is that as the larger particles grow at ever greater rates, compared to smaller particles, multimodal distributions can arise when there is severe asymmetry between the number of particles that grows into a size range (slow) and those that grow out of it (rapid). Tojo et al (1997) also reported this in their simulation studies.…”
Section: Effect Of Initial Reactant Ionmentioning
confidence: 62%
“…[1][2][3] Luminescence tagging and imaging, medical diagnostics, drug delivery, and nanoelectronics are some of the applications that are being developed with these nanomaterials. [4][5][6][7][8] One of the approaches utilized to synthesize these nanomaterials is the microemulsion-templated method using compressed gases as solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Figure 6 shows a representative excitation and emission spectra of the stabilized CdS nanoparticles obtained at two different densities of scCO 2 . A red shift of 14 nm (from 349 to 363 nm) together with an increment in the Full Width at Half Maximum (FWHM) from 48 to 63 nm, was observed in the excitation spectra when the density of the solvent decreased from 0.92 to 0.87 g mL À1 (W = 10 F-AOT concentration 10 mm).…”
mentioning
confidence: 99%